Performance of Low-Cost Agar from Gracilaria salicornia on Tissue Culture of Pleurotus HK-37 - Farid Mzee Mpatani; Said Ali Hamad Vuai (The Scientific World Journal)
Currently, the demand of Pleurotus HK-37 (oyster mushroom) in Tanzania is growing rapidly due to the increasing of awareness on its nutrition, health, and economic benefits. Despite the increasing demand, the availability of strains of Pleurotus HK-37 species is still a challenge due to high cost of tissue culture technology. The high cost of importing agar seems to be among the factors for this failure. This study aimed at investigating the performance of low-cost agar from local Gracilaria salicornia on tissue culture of Pleurotus HK-37. Local extracted agars with different gel strengths ranging between 100, 200, 300, 400, and 500 g/cm2 were used to make PDA media. The average mycelia growth rate (mm/day) ranged between 9.87 ± 1.44 and 14.9 ± 0.85 mm/day. Low-cost agar shows quite similar performance as that of standard agar on active growth of Pleurotus HK-37 mycelia. All PDA plates appeared white and feathery and showed to grow in a circular mode (radial extension). Mycelia growth on standard agar PDA took 5 days while on extracted local agar PDA took 5 to 7 days to fully colonize the plate at 27 ± 2°C. The present study shows that the production cost can be reduced by ∼35–78% by using local agar.